QUALITY CHARACTERISTICS OF CANNED CRAB PROCESSING (Portunus pelagicus) - Sipahutar, Yuliati Hotmauli; Dijaya, Ganis Aprila; Afifah, Rufnia Ayu; Arif, Galih AF (Aurelia Journal, 2024)
Crab is a fishery commodity that has high economic value. This research aims to determine the quality characteristics of the canned crab processing, which consists of: processing process flow, quality testing of raw materials and final products, application of temperature, yield, productivity and waste management. Data collection using observation, interviews and company documentation. Data analysis using comparative descriptive. The research results show that pasteurization of crab in cans goes involve 14 process stages starting from receiving raw materials to delivery. The organoleptic quality test result for raw materials and final products were 8,16 and 8,25. The results of microbiological test according to SNI, namely the TPC of raw materials and final products is 3.4 x 104 and 11 x 103 col/g. E. coli, Salmonella, S. aureus, V. cholerae were negative, there were no foreign body findings. The Chloramphenicol (CAP) test results for raw materials and final products were 0.015 and 0.012 ppb. Total weight for Jumbo Black can 96.46%, Lump Black Can 96,97%, Lump Seawings 96,25%, Claw Meat 94.48% and Cocktail 98.46%. The application of temperature has been good, namely receiving raw materials 1,35°C, sorting 3,28°C, Darkroom checking 3,53°C, Mixing 6,43°C, Filling and weighing 5,34°C and Closing cans 9,16°C. The yield at the picking stage was 32,8% and the sorting stage was 96,02%.  Productivity at the Special meat and Claw meat sorting stage reached 1,92 kg/hour/person and the filling and weighting stage was 20,5, cans/hour/person. Shell's solid waste is sold for animal feed, liquid waste is processed through the Waste Water Treatment Plant.